Strategic Use of the Twitter/X Account @hivaidspimsid as a Government HIV/AIDS Prevention Tool - Nita Aribah Hanif; Irham Maulida; Aziz Reza Randisa; Asriadi (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study analyzes the strategic use of the Twitter/X account @hivaidspimsid as a government HIV/AIDS prevention tool. This research method uses qualitative content analysis. The 280-character data were obtained from the government's Twitter/X account (@hivaidspimsid) from April 2021 to September 2022. The selection criteria focused on issues covering HIV/AIDS education, prevention, and treatment, awareness campaigns, community interaction, and issues of stigma or discrimination. This research data analysis used NVivo 12 Plus software. The results of this study indicate that the government Twitter/X account @hivaidspimsid peaked in July-September 2021, with 55.26% of the campaign information on HIV/AIDS prevention efforts provided, and decreased in July-September 2022 to 5.25%. The X account @hivaidspimsid's activity conveyed messages to increase public knowledge about HIV/AIDS through education, prevention campaigns, testing and treatment promotions, and correcting hoaxes, by encouraging early detection and healthy living. Frequent conversations on the @hivaidspimsid account revolved around HIV, health, films, testing, and treatment. This is relevant to the important hashtags on the @hivaidspimsid account, which include HIV (23.58%), I Am Brave (19.51%), and HIV/AIDS (5.69%). Furthermore, SayaBerani.id and the Indonesian Ministry of Health were also frequently mentioned on the @hivaidspimsid account. The DKI Jakarta area is a central location for accounts that interact extensively with the @hivaidspimsid account.